The Effectiveness of Treating Anxiety with Reiki - Humphreys Erika; Cabrera Emily; Downey Luhrmann Susan (Journal of Behavior Therapy And Mental Health, 2023)
The effectiveness of treating anxiety with Reiki is explored within ten quantitative studies. Methodology utilized for a critical appraisal and systematic review of the literature is explained with inclusion and exclusion criteria. Theoretical framework for the project is grounded in the work of Hildegard Peplau, whose nursing theory based on the therapeutic use of self is foundational for Reiki implementation. A thorough critique of the literature is conducted for key components of robustness and believability. This critique is conducted using a structured guide addressing synthesized strengths and weaknesses of the body of literature. A synthesis of the literature explores the findings of the studies. This synthesis reports on Reiki’s effectiveness in treating anxiety within a variety of patient settings and populations, its effect on subscales of anxiety, physiological manifestations of anxiety and pain associated with anxiety. Cultural considerations effecting Reiki’s potential effectiveness are discussed. Gaps in the literature are examined, including the studies’ narrow sample population, lack of participant exclusionary factors for controlled outcome data, and the lack of studies across time. Implications for future research are discussed with recommendations for expanded research that includes a broader variety of settings, age groups, and patient diagnoses, including anxiety disorders, for research data that is transferable. Implications for further practice for the advanced practice registered nurse (APRN) are explored, with the potential benefits for both providers and patients, including improved patient satisfaction and expansion of provider treatment modalities.
Keywords: Reiki